INFLUENCE OF DEXAMETHASONE-MODIFIED DENDRITIC CELLS GENERATED WITH IFNα UPON AUTOLOGOUS T LYMPHOCYTE FUNCTIONS IN THE PATIENTS WITH RHEUMATOID ARTHRITIS - Yu. D. Kurochkina; T. V. Tyrinova; O. Yu. Leplina; M. A. Tikhonova; A. E. Sizikov; A. E. Sulutian; O. A. Chumasova; A. A. Ostanin; E. R. Chernykh (Медицинская иммунология, 2019)
Dendritic cells (DCs) play a key role in maintaining the peripheral tolerance of lymphocytes to autoantigens. Recovery of immunological tolerance in autoimmune diseases, particularly, in rheumatoid arthritis (RA) is considered a new therapeutic strategy. The aim of this work was to study the effect of dexamethasone-modified DCs generated from monocytes of RA patients in the presence of IFNα (DCsDex), upon autologous T lymphocytes in mixed leukocyte culture (auto-MLC), and to investigate possible mechanisms of the DCsdex tolerogenic effect upon autoreactive T cells. We have shown, that DCsDex from RA patients induce T cell hyporeactivity in auto-MLC. Hyporeactivity of T cells is associated with cell cycle blockage in CD4+T lymphocytes and decreased IFNγ, IL-17, IL-4 and IL-13 production, which indicates the induction of CD4+T cell anergy. In this case, inhibition of Th1/Th17 has been more pronounced than the suppression of Th2 cells producing IL-4 and IL-13. Along with T cell anergy, the decrease of proliferative response in auto-MLC is associated with increased CD3+T lymphocyte apoptosis. In addition, the DCsDex of RA patients suppresses the proliferation of autologous T cells stimulated by unmodified DCs. This effect is associated with enhancement of IL-10-producing CD4+T cells in the auto-MLC, thus being indicative for an ability of DCsDex to induce conversion of CD4+T lymphocytes into regulatory T cells (Tr1). The data obtained characterize a new type of tolerogenic DCs, generated from blood monocytes of RA patients in the presence of IFNα and modified by dexamethasone, thus revealing a mechanism for tolerogenic effect of DCsDex upon T cells that recognize self-antigens in auto-MLC.